2022
DOI: 10.5435/jaaos-d-21-00432
|View full text |Cite
|
Sign up to set email alerts
|

Bicondylar Tibial Plateau Fractures: What Predicts Infection?

Abstract: Objectives:The purpose of this study was to identify the patient, injury, and treatment factors associated with infection of bicondylar plateau fractures and to evaluate whether center variation exists.Design:Retrospective review.Setting:Eighteen academic trauma centers.Patients/participants:A total of 1,287 patients with 1,297 OTA type 41-C bicondylar tibia plateau fractures who underwent open reduction and internal fixation were included. Exclusion criteria were follow-up less than 120 days, insufficient doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Olszewski, Nathan MD, Manzano, and Givenchy MD et al reported in their series that 101/1287 (7.8%) patients developed an infection. They found that temporary external fixation was a risk factor (OR 2.07; p = 0.013) associated with infection [ 14 ]. The current study evaluated the safety and efficacy of early definitive ORIF followed by ciNPT use in Schatzker type IV–VI TPFs compared to staged treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Olszewski, Nathan MD, Manzano, and Givenchy MD et al reported in their series that 101/1287 (7.8%) patients developed an infection. They found that temporary external fixation was a risk factor (OR 2.07; p = 0.013) associated with infection [ 14 ]. The current study evaluated the safety and efficacy of early definitive ORIF followed by ciNPT use in Schatzker type IV–VI TPFs compared to staged treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Data on infections associated with knee dislocation are scarce in the literature, but existing data also report a low rate of infection [10]. However, the rate of surgical site infections is increasing with regard to secondary surgical treatments and potential bony, vascular or nerve interventions and can reach rates of up to 10%, depending on patient-and treatment-related risk factors [20,22]. A higher percentage was reported for posttraumatic cartilage lesions, with 41.7% (n = 50) in our data set.…”
Section: Limitation In Everyday Lifementioning
confidence: 99%